Phenotyping and genotyping of cassava F1 population (CTS family) for mapping drought tolerance QTLs based on RAD Sequencing 3704 - Bedoya-Moreno, María Alejandra; Bohorquez-Chaux, Adriana; Barrera-Enríquez, Vianey; Zhang, Xiaofei (2022)
The drought phenomenon is currently one of the main climatic problems that affects all types of crops around the world. Cassava is a crop of great importance in the tropics because it plays a relevant role in food security and in industrial processes; therefore, knowing the tolerance to abiotic phenomena such as drought allows generating breeding programs to obtain resistant genotypes. In addition to identifying traits that plants subjected to water deficit can develop and relating this type of results with genetic information.